Big data analytics in traffic and transportation engineering emerging research and opportunities - Moridpour, Sara, 1980- (Engineering Science Reference, 2019)
"This book identifies the factors contributing to the severity of vehicle-pedestrian crashes at mid-blocks. It examines the influence of the socioeconomic factors of the neighborhoods where road users live (residency neighborhood) and where crashes occur (crash neighborhood) on vehicle-pedestrian crash severity, while controlling for the influences of roadway, road user, vehicle and environmental factors"--Provided by publisher.